Komunikasi Massa dan Sosialisasi - Manap Solihat (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The research on media impact has already been numerous and some theories of media impact overcome its doubt. Research on the media impact of socialization, however is rarely conducted since it is difficult to determine the parameters. The socializations itself is a time consuming process. The research is intended to describe behaviour pattern related to the programmes in the media namely news programme, that is to find out the response, to describe students behaviour in using the information from television, to know studens responses in waching news programme through socialization, to find out involvement (impact) of gender variable toward the habis in waching news programme. The research shows that: news programme plays a role as complementer information source for student to know politic about government board, like executive, legislative or yudicative board; students try to find information not only from one channel but also from other private –owned channels as alternative to get information; based on this research, parent friends and school environment will play important role on the level of knowledge realization about credible politic. The analisys shows that gender can influence response from students in waching news. Through students socialization, the impact of news programme, impact more to men than women. Before probing this research further, it should be noted that socialization values mentioned here are not a real political participation (for example by participating in one of the political party). The socialization is meant as an attempt to shape thought, attitude and behaviour orientations on certain values which later develop as internalization process.